Perbandingan Mata Pisau Cutter, Silet, Pisau Ukir Kayu dan Pisau Blender Daging Untuk Mesin Pencacah Plastik Kemasan 220ml Portable - Yuyu Nofriyanto; Subkhan Subkhan; Yang Fitri Arriyani (Jurnal Inovasi Teknologi Terapan, 2026)
This study aims to compare the performance of four types of blades, namely cutter knives, razor blades, wood carving knives, and meat blender knives, on a 220 ml portable plastic packaging shredder. The research was conducted through experimental testing to determine the durability and cutting efficiency of each type of blade under workload during the shredding process. The test results showed that the wood carving knife had the best performance with a cutting force of 1 N, producing the highest number of cuts, totaling 41 plastic cups compared to the other knives. The cutter knife ranked second with 38 cuts, while the razor blade and meat blender knife showed the lowest results. The combination of an optimal wedge angle and low cutting force makes the wood carving knife the most efficient choice for a portable plastic shredder. The results of this study are expected to serve as a reference in selecting effective and economical blades to support small and medium scale plastic waste recycling process.